Pengaruh Promosi di Media Sosial Instagram Terhadap Minat Beli Konsumen Ukir Pecah (Mahasiswa Universitas Trunojoyo Madura) - Candra Wahyu Wibowo; Nirma Kurriwati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the effect of Instagram social media on buying intention in Ukir Pecah products among Trunojoyo University students, Madura. The method used in this research is to use a quantitative approach, the subjects in this study are students of Trunojoyo University, Madura. Sampling in this study using accidental sampling with a total of 99 respondents, and analysis using simple linear regression analysis. Sources of data in this study are primary data and secondary data. The data in this study were collected using a questionnaire technique, and after the data was collected, the researchers processed the data and the results from the calculated data, the authors drew conclusions. The results of this study are used to explain the influence of Instagram social media on consumer buying interest. The hypothesis in this-study is that-social-media Instagram has-a-significant-effect-on the Buying-Interest of Carving Broken consumers. It was found that the variable (X) namely social-media had a value of tcount ttable (20,0671,987). The-results of this study prove that the-independent variable, namely-the promotion in social-media-variable,-has-a-positive influence on-the dependent variable, namely the consumer buying interest variable.